Еfficiency of innovative methods for training for social work in the Republic Kazakhstan (The Journal of Psychology and Sociology, 2012)
Efficiency of use of innovative methods to train specialists in social work in Republic of Kazakhstan.This article is devoted to problems of effectiveness of the training of social workers in the context of the realities of modern Kazakhstani education. Quantitative and qualitative indicators Criteria, efficiency indicators of social work are to be analyzed. The major guidelines of social work in Kazakhstan and specificity of educational activity in this direction are identified. Its modification in the context of changes in the life of the modern Kazakh society is presented.
Keywords: innovative methods; indicators of performance of social work; professional social worker.